Mental health leadership perspectives on self-direction. Issue 4 (4th July 2018) - Croft, Bevin; Simon-Rusinowitz, Lori; Loughlin, Dawn M; Mahoney, Kevin J.
ABSTRACT: Self-direction is a model for organizing services and support in which the service user is at the center of an individualized budgeting and planning process. Mental health program directors are key in self-direction's adoption and implementation, and understanding their views is critical. Using a descriptive cross-sectional study, the researchers in this current study used a survey ( n  = 46) and interviews ( n  = 17) to gauge expectations for self-direction and to identify barriers and facilitators for adoption and implementation. Respondents evinced strong interest in self-direction and endorsed its potential to support well-being and improve mental health service quality. Respondents also voiced concerns, including competing agency priorities, provider resistance, and administrative challenges.